Bias correction and downscaling of future RCM precipitation projections using a MOS‐Analog technique. Issue 5 (6th March 2017) - Turco, M.; Llasat, M. C.; Herrera, S.; Gutiérrez, J. M.
Abstract: In this study we assess the suitability of a recently introduced analog‐based Model Output Statistics (MOS) downscaling method (referred to as MOS‐Analog) for climate change studies and compare the results with a quantile mapping bias correction method. To this aim, we focus on Spain and consider daily precipitation output from an ensemble of Regional Climate Models provided by the ENSEMBLES project. The reanalysis‐driven Regional Climate Model (RCM) data provide the historical data (with day‐to‐day correspondence with observations induced by the forcing boundary conditions) to conduct the analog search of the control (20C3M) and future (A1B) global climate model (GCM)‐driven RCM values. First, we show that the MOS‐Analog method outperforms the raw RCM output in the control 20C3M scenario (period 1971–2000) for all considered regions and precipitation indices, although for the worst‐performing models the method is less effective. Second, we show that the MOS‐Analog method broadly preserves the original RCM climate change signal for different future periods (2011–2040, 2041–2070, 2071–2100), except for those indices related to extreme precipitation. This could be explained by the limitation of the analog method to extrapolate unobserved precipitation records. These results suggest that the MOS‐Analog is a spatially consistent alternative to standard bias correction methods, although the limitation for extreme values should be taken with caution in cases where this aspect is relevant for the problem. Key Points: We assess the analog‐based Model Output Statistics (MOS) downscaling method for climate change studies The MOS‐Analog downscaling method is a spatially consistent alternative to standard bias correction methods The downscaled results broadly preserve the original RCM climate change signal, except for extreme precipitation indices